ЭТИО-ПАТОГЕНЕТИЧЕСКАЯ КЛАССИФИКАЦИЯ СЕКСУАЛЬНЫХ РАССТРОЙСТВ У МУЖЧИН (Вестник урологии)
The lecture presented a methodology for assessing sexual health and staging sexological diagnosis. Based on the assessment of the vast clinical material (more than 20 000 patients during over 18 years ) the main clinical forms of sexual disharmony in men are presnted, as well as the frequencyof certain forms and their etiopathogenetic study. It also gives examples of sexological diagnoses and methods of statistical encryption, according to ICD-10.